An Analysis of Attitude and Graduation of Evaluative Language Produced by Mike Chen as A Food Vlogger in YouTube - Putri Lioda Vebrina; Hamzah Hamzah (Universitas Negeri Padang, 2019)
In general, culture is believed to be the identity of a nation and culture influences human thought patterns and speech acts. This study aims to explain and find out the evaluative language produced by a food vlogger (video blogger) or YouTube user with the content about reviewing food. The object of this study is Mike Chen who was born in China. The method used in this research is a descriptive research. In this study the evaluative language produced by Mike Chen is presented by using appraisal theory. The source data of this research was obtained from five videos of Mike Chen YouTube account. All utterances produced by Mike Chen were transcribed into text as data analysis. The finding of this study revealed that the most prominent aspect in the attitude element is the appreciation and the most prominent aspects in the graduation element are intensifier and metaphorical.